2017
DOI: 10.1007/s12070-017-1209-z
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Children with Anomalous Cochleovestibular Anatomy: Our Experience

Abstract: To report operative findings, postoperative course, and postimplantation performance in patients with cochlear malformations who underwent cochlear implantation. Seventeen patients with malformations which included enlarged vestibular aqueduct (n = 6), Mondini's dysplasia (n = 5) common cavity deformity (n = 3) and incomplete partition type 2 (n = 3) underwent cochlear implantation with Nucleus 22 straight array device at our center. Operative findings described facial nerve anatomy and cerebrospinal fluid lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 12 publications
(14 reference statements)
1
23
0
Order By: Relevance
“…Early on in the protocol, all cochleovestibular anomalies detected on MRI would receive HRCT including IP2. Although HRCT would be indicated to complete diagnostic evaluation by our neuroradiologist, in the absence of a concurrent craniofacial syndrome, it is very rare that an abnormal facial nerve is present with an IP2 cochleovestibular anomaly . Therefore, it was determined that such imaging was not required to facilitate a safe and efficient surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Early on in the protocol, all cochleovestibular anomalies detected on MRI would receive HRCT including IP2. Although HRCT would be indicated to complete diagnostic evaluation by our neuroradiologist, in the absence of a concurrent craniofacial syndrome, it is very rare that an abnormal facial nerve is present with an IP2 cochleovestibular anomaly . Therefore, it was determined that such imaging was not required to facilitate a safe and efficient surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Several ways of controlling an intraoperative gusher have been reported; the most common way is to wait until the gusher stops, insert the array, and meticulously pack the cochlear opening with muscle, fascia, and sometimes also fibrin glue 5 , 7 , 13 , 14 or, in cases of severe malformation, fat tissue instead of muscle. 14 Indeed, this method continues to be used because it is largely effective at preventing postoperative complications due to CSF leakage, even in CI recipients who did not receive a FORM array.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Indeed, this method continues to be used because it is largely effective at preventing postoperative complications due to CSF leakage, even in CI recipients who did not receive a FORM array. 5 , 7 , 13 , 14 However, to the best of our knowledge, Sennaroglu et al is the only study which assessed within one study the effectiveness of the cork-type array (the FORM's predecessor) and standard straight arrays in preventing postoperative CSF leak. They found that 20.7% (6/29) implanted with a straight array experienced postoperative rhinorrhea after a gusher; in contrast, only 4.2% (1/24) implanted with the cork-type array had either of these complications postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other studies reported a variable CI surgery outcome among patients based on types of inner ear anomalies [2,4,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Several authors reported that patients who have mild anomalies such as EVA and IP II have a better outcome than patients who have severe malformations such as a common cavity [4,[24][25][26][27][28]31]. Nevertheless, Tay et al has concluded that the outcome of patients who have an absent cochlear nerve, electrode folding and underlying neurological disorders is poor [37].…”
Section: Literature Reviewmentioning
confidence: 99%